Managing Subacute Subperiosteal Hematoma with High Intraocular Pressure: A Case Report - SE, Hashim; A, Fatisha; MN, Nazri (IIUM Medical Journal Malaysia, 2017)
Subperiosteal haematoma of the orbit is an uncommon complication of maxillofacial trauma, hence easily missed. It usually presents subacutely with proptosis and diplopia. In our case, the subperiosteal haematoma is complicated with high intraocular pressure, necessisating measures to reduce the intraocular pressure. Unresponsive to only medical treatment, surgical evacuation was carried out in this patient. Removal of the clot finally relieved the intraocular pressure and simultaneously improved the proptosis and the cumbersome diplopia.